Cambodia : Using Contracting to Reduce Inequity in Primary Health Care Delivery - Schwartz, J. Brad; Bhushan, Indu (World Bank, Washington, DC, 2013)
This study examines the equity impact of using private sector contracts for the delivery of primary health care as an alternative to traditional government provision in Cambodia. It does so by using pre- and post intervention data from a large scale contracting experiment to provide primary health care in rural districts of Cambodia between 1998 and 2001. Equity as well as coverage targets for primary health care services were explicitly included in contracts awarded in five of nine rural districts with a population totaling over 1.25 million people. The remaining four districts included in the test were given identical equity and coverage targets and used the traditional government provision of services. After two-and-a-half years of the trial, the results suggest that although coverage of primary health care services in all districts had substantial increases, people in the poorest one-half of households living in contracted districts were more likely to receive these services than similarly circumstanced poor people in government districts, other factors equal.